Pelatihan pembuatan video profil sekolah di SMA se-kabupaten Lombok Timur - Kholida Ismatulloh; Jamaluddin Jamaluddin; Yosi Nur Kholisho; Baiq Desi Dwi Arianti; Rasyid Hardi Wirasasmita; Muhammad Zamroni Uska; Samsul Lutfi (Universitas Hamzanwadi, 2023)
The rapid development of science and technology, along with the advent of the Fourth Industrial Revolution and Society 5.0, has significantly impacted all aspects of life, including education. In response to these developments, the Ministry of Education and Culture has strengthened the teaching of informatics in the latest curriculum,